Comparative Study On Intestinal Flora Of The Type Ii Diabetes Mellitus Patients. - Kumar T, Senthil; Merina, Sahaya; Ranjitha, Ranjitha; Raj V, Shaman; S, Shasi (Journal of Neonatal Surgery, 2025)
Background: To study the Intestinal flora of the regularly medicated Type II Diabetes Mellitus patients. To analyse the comparative study of Type II Diabetes Mellitus patients with the normal Intestinal flora. To study the Drug sensitivity of the intestinal flora to anti-diabetic drugs. Isolation of the intestinal flora using culture media. Methods: The micro-organisms are cultured using culture media like DCA (Deoxycholate citrate agar), XLD (Xylose lysine Deoxycholate) and MacConkey agar. Biochemical tests like Indole test, TSI, urease utilization, Citrate utilization are used to determine the species of the organisms. Study takes place in Central laboratory of A.C.S. Medical College & Hospital. A Comparative study with the period of the study Six (6) months and Sample size is 30 Faeces samples with the Inclusion criteria: Faecal samples of the diabetic patients under regular antidiabetic medication, Exclusion criteria: Faecal samples of non-medicated diabetic patients and normal human. Results: In total of 30 Patients, 15 diabetic patients and 15 normal patients’ sample were taken and processed. In those diabetic patients has less E.colidominance and has Klebsiella Dominance. E.coli was sensitive to anti diabetic drug like metformin. Conclusion: This study is done to find the changes in the regularly medicated patients and how it is changed. The intestinal flora is sensitive to the drugs and regular medication can degrade the intestine and high doses can cause permanent degradation in the intestinal flora. The regular medication can inflammable to intestine and can regenerate by the indigenous system of the medicine and the intestinal environment is maintained by the natural medication.